Mechanistic insights into the role of herpes simplex virus 1 in Alzheimer’s disease - Feng, Shu; Liu, Yongzhen; Zhou, Yu; Shu, Zhenfeng; Cheng, Zhuxi; Brenner, Charles; Feng, Pinghui (Frontiers in Aging Neuroscience, 2023)
Alzheimer’s Disease (AD) is an aging-associated neurodegenerative disorder, threatening millions of people worldwide. The onset and progression of AD can be accelerated by environmental risk factors, such as bacterial and viral infections. Human herpesviruses are ubiquitous infectious agents that underpin numerous inflammatory disorders including neurodegenerative diseases. Published studies concerning human herpesviruses in AD imply an active role HSV-1 in the pathogenesis of AD. This review will summarize the current understanding of HSV-1 infection in AD and highlight some barriers to advance this emerging field.